The Role of Chaos in Poverty and Children's Socioemotional Adjustment - Evans, Gary W.; Gonnella, Carrie; Marcynyszyn, Lyscha A.; Gentile, Lauren; Salpekar, Nicholas (Psychological Science, 2005)
There are growing levels of chaos in the lives of American children, youth, and families. Increasingly, children grow up in households lacking in structure and routine, inundated by background stimulation from noise and crowding, and forced to contend with the frenetic pace of modern life. Although widespread, chaos does not occur randomly in the population. We document that low-income adolescents face higher levels of chaos than their more affluent counterparts and provide longitudinal evidence that some of the adverse effects of poverty on socioemotional adjustment are mediated by exposure to chaotic living conditions.